Multiple solutions to a quasilinear periodic boundary value problem with impulsive effects - John Graef; Shapour Heidarkhani; Lingju Kong; Shahin Moradi (Electronic Journal of Qualitative Theory of Differential Equations)
The authors investigate the multiplicity of solutions to a quasilinear periodic boundary value problem with impulsive effects. They use variational methods and some critical points theorems for smooth functionals, due to Ricceri, that are defined on reflexive Banach spaces. They obtain the existence of at least three solutions to the problem. The applicability of the results is illustrated with an example.